Occupational safety and health management system: practical guide for implementation - Basiran, Aziz; Baharudin, Mohd Rafee; Anwar, Fakhrul (McGraw-Hill Education (Asia), 2015)
This book is written for individuals with a real interest in occupational safety and health management systems (OSHMS). It is useful for students in secondary schools or those on the road to get their certificate, diploma, degree, masters or doctorate. It is of definite use for OSH practitioners, professionals, OSH management representatives, safety and health officers, safety and health committee members, auditors, consultants, trainers and lecturers. In this book, you will learn how to establish an OSHMS through a step by step guide for implementation. A variety of examples provided in this book will give you a better understanding of each of those steps. Occupational Safety & Health Management System is an all-inclusive book covering the fundamental principles of OSHMS for certification. It explains the step by step approach in establishing, implementing, maintaining and continually improving each element of OSHMS. This book will be invaluable for OSH practitioners and professionals, OSH management representatives, safety and health officers, safety and health committee members, auditors, consultants, trainers as well as students pursuing OSH qualifications in tertiary institutions.